THE NATURE OF SURFACE FRIABLE SEDIMENTS AND MODERN EXOGENOUS PROCESSES OF THE DILIJAN BASIN: (the basin of the middle course of the Aghstev River, Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The granulometric, mineralogical, chemical, and spectral compositions of eluvium, deluvium, and defluction formations, as well as the physico-mechanical properties of landslide soils, have been determined, which makes it possible to distinguish to a certain extent between different genetic types of loose accumulations and the conditions of their formation. According to the topographic map on a scale of 1:25 000, the orders of the main tributaries of the Aghstev River are determined – all of them have the fourth order. Of the exogenous processes, landslides and partial demolition of weathered loose material from the slopes during heavy rains are the most dangerous for the basin. The complex geological and geomorphological structure of the Dilijan basin contributes to its instability in the future and increases the risk of activation of dangerous natural processes: a variety of rocks that become exposed during weathering, as well as clays of different ages and origins, which facilitate the formation of new landslides; the presence of faults of different ranks, contributing to the instability of rocks on the steep slopes of the basin; large falls in the channels of the main tributaries of the Aghstev River and numerous ravines, in which strong winds mudflows may form in heavy rains; the geographical location of the basin itself is within an intensely differentiated arch-block zone.
Keywords: clay; landslide; slope; stream gradient; stream order